2011
DOI: 10.3949/ccjm.78a.11025
|View full text |Cite
|
Sign up to set email alerts
|

Nocturia in the elderly: A wake-up call

Abstract: Nocturia is a condition that health providers must seek out and address in older adults. Since it adversely affects quality of life and carries a risk of morbidity and of death (often because of falling), this symptom must be elicited during the physician-patient encounter. Understanding its underlying causes, risk factors, and consequences is essential in formulating the most suitable management strategy. Drug and nondrug treatments target the individual disorders that contribute to nocturia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
(54 reference statements)
0
14
0
Order By: Relevance
“…In a Chinese study, BPH was found to induce nocturia by decreasing nocturnal bladder capacity with advancing age [ 26 ] . …”
Section: Discussionmentioning
confidence: 98%
“…In a Chinese study, BPH was found to induce nocturia by decreasing nocturnal bladder capacity with advancing age [ 26 ] . …”
Section: Discussionmentioning
confidence: 98%
“…Paxerol is a novel proprietary IR/SR (50%:50%) formulation of PG inhibitors (acetaminophen and ibuprofen). Inhibition of the PG pathway is expected to alleviate nocturia because PGs are local modulators of reflex micturition, increase detrusor muscle tone, enhance micturition, and inhibit antidiuretic hormone . One‐half of the drugs is released via IR during the first hour to provide “loading dose” effect.…”
Section: Discussionmentioning
confidence: 99%
“…PG‐E2, PG‐E2α, PG‐E1, and thromboxane A2 have been shown to cause contraction of isolated detrusor muscle in the bladder . Cyclo‐oxygenase‐2 inhibitors and PG inhibitors such as Nonsteroidal Anti‐Inflammatory Drugs (NSAIDs) reduce urine production, detrusor muscle tone and inflammation, especially in men with benign prostatic hyperplasia (BPH) …”
Section: Introductionmentioning
confidence: 99%
“…Nocturnal polyuria (NP), or excessive overnight urine production, is a highly prevalent but often underreported underlying cause of nocturnal enuresis in children, nocturia in adults and nocturnal incontinence in older persons . It is the result of an impaired circadian rhythm of hormones regulating water and solute handling by adjusting renal blood flow and solute reabsorption.…”
Section: Introductionmentioning
confidence: 99%